2005
DOI: 10.1007/s00125-005-0002-9
|View full text |Cite
|
Sign up to set email alerts
|

Renal hyperfiltration in type 2 diabetes: effect of age-related decline in glomerular filtration rate

Abstract: Aims/hypothesis: We sought to characterise the effect of the age-related decline of GFR on hyperfiltration in type 2 diabetes and to identify clinical characteristics associated with hyperfiltration. Materials and methods: GFR was measured in 662 type 2 diabetic patients by plasma disappearance of 99 m-technetium-diethylene-triaminepenta-acetic acid. The prevalence of hyperfiltration was calculated using both an age-unadjusted GFR threshold of >130 ml min −1 1.73 m −2 and an age-adjusted threshold incorporatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 51 publications
4
56
2
Order By: Relevance
“…The presence of persistent proteinuria was a strong risk factor for subsequent loss of GFR, as shown by our findings that 75.6% of our patients had proteinuria and 16.5% reached ESRD, re-emphasizing earlier reports that established the importance of sustained increases in urine albumin excretion in the pathogenesis and diagnosis of diabetic kidney disease 13–1620. This is considerably higher than the reported rate in diabetic Pima Indians, with 15% progressing to ESRD at approximately 20 years of diabetes 26.…”
Section: Discussionsupporting
confidence: 89%
“…The presence of persistent proteinuria was a strong risk factor for subsequent loss of GFR, as shown by our findings that 75.6% of our patients had proteinuria and 16.5% reached ESRD, re-emphasizing earlier reports that established the importance of sustained increases in urine albumin excretion in the pathogenesis and diagnosis of diabetic kidney disease 13–1620. This is considerably higher than the reported rate in diabetic Pima Indians, with 15% progressing to ESRD at approximately 20 years of diabetes 26.…”
Section: Discussionsupporting
confidence: 89%
“…The reference value iGFR was obtained by measuring the plasma disappearance of 99m Tc-diethylene-triamine-pentaacetic acid employing the Brochner-Mortensen correction [3]. Urinary albumin and serum electrolytes were measured as described previously [3].…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…Urinary albumin and serum electrolytes were measured as described previously [3]. Creatinine was measured on an automatic analyser (Hitachi 911; Roche Diagnostics, Mannheim, Germany), which produces creatinine values that fall within less than ±15% of the reference MDRD method.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…In older patients with type 2 diabetes, hyperfiltration can be masked by this age-related decline in GFR. We documented the prevalence of hyperfiltration with and without adjustment for age in patients with type 2 diabetes in a clinic-based cross-sectional study of 662 patients with type 2 diabetes [28]. The overall prevalence of hyperfiltration was 7.4% without age correction and 16.6% after adjustment for age (Fig.…”
Section: Hyperfiltration In Type 2 Diabetesmentioning
confidence: 99%
“…The age-unadjusted threshold for hyperfiltration was defined arbitrarily as a BrochnerMortensen corrected GFR of >130 ml min −1 1.73 m −2 . To account for the age-related decline in GFR, hyperfiltration was defined as GFR >130 ml min −1 1.73 m −2 minus 1 ml min −1 1.73 m −2 per year after the age of 40 [28]. Studies in hypertensive non-diabetic participants, using creatinine clearance as an index of GFR, have suggested that elevated GFR may be an indicator of early target organ damage [37,38].…”
Section: Hyperfiltration Independent Of Diabetesmentioning
confidence: 99%